Sistem Irigasi Pertanian Masa Majapahit dan Sumbangannya pada Kemakmuran Negara - Maharani, Raihana Ayu; Haliza, Roro Citraning Nur; Zakaria, Alfan Ghafar; Zahro, Nur Azkiyatuz; Diwangkara, Rakanda Paritusta; Nugrahani, Djaliati Sri (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The success of agriculture lies in the condition and management of the land, irrigation system, and the participation of the community. It refers to prosperity not only to farmers, but also to the country. The first modern agricultural system in Indonesia was established in the Majapahit era. The agricultural system has advanced and played an important role in contributing prosperity at that time so that it can be revitalized in the present. The purpose of this study is to understand the agricultural irrigation system during the Majapahit period based on inscription and artifact data in Trowulan, analyze the relationship between agricultural irrigation systems and Majapahit prosperity, and identify Majapahit irrigation systems that can be applied in the present. Data retrieval methods are online and offline. Online data retrieval is done with literature, while offline is done with observations, field surveys, and interviews. The data analysis technique in this study is qualitative descriptive. The progress of the Majapahit irrigation system is evidenced by the existence of various archaeological and non-artifactual dwellings. Some artifactual evidence such as terracotta pipelines, canals, old reservoirs, artificial ponds, and temple reliefs. While non-artifactual evidence can be seen in various inscriptions, books, and ancient literary works. Geographical conditions that support causing agriculture to grow rapidly so that the Majapahit agricultural system has a considerable role related to prosperity. Majapahit irrigation system that can be reapplied in the present is an underground irrigation system that is more effective and suitable in areas that have a relatively dry climate. There are several challenges in its application such as the existence of linggan and climate change. === Keberhasilan pertanian terletak pada kondisi dan pengelolaan tanah, sistem irigasi, dan peran serta masyarakat yang melaksanakan. Dampaknya dapat membawa kemakmuran bukan hanya bagi para petani, tetapi juga negara. Sistem pertanian modern pertama di Indonesia terdapat pada era Majapahit. Sistem pertanian tersebut sudah maju dan berperan penting dalam menyumbang kemakmuran pada masa itu sehingga dapat direvitalisasi untuk diterapkan kembali di masa kini. Tujuan dari penelitian ini yaitu memahami sistem irigasi pertanian pada masa Majapahit berdasarkan data prasasti dan artefaktual yang ada di Trowulan, menganalisis hubungan antara sistem irigasi pertanian dengan kemakmuran Majapahit, dan mengidentifikasi sistem irigasi Majapahit yang dapat diterapkan di masa kini. Metode pengambilan data dilakukan secara daring dan luring. Pengambilan data secara daring dilakukan dengan literatur, sedangkan secara luring dilakukan dengan observasi, survei lapangan, dan wawancara. Teknik analisis data dalam penelitian ini adalah kualitatif deskriptif. Kemajuan sistem irigasi Majapahit dibuktikan dengan adanya berbagai tinggalan arkeologis artefaktual dan non artefaktual. Beberapa bukti artefaktual seperti pipa saluran berbahan terakota, kanal, waduk tua, kolam buatan, serta relief-relief candi. Sedangkan bukti non artefaktual dapat dilihat pada berbagai prasasti, kitab-kitab, dan karya sastra kuno. Kondisi geografis yang mendukung menyebabkan pertanian berkembang pesat sehingga sistem pertanian Majapahit memiliki peran yang cukup besar terkait dengan kemakmuran. Sistem irigasi Majapahit yang dapat diterapkan kembali di masa kini adalah sistem irigasi bawah tanah yang lebih efektif dan sesuai pada daerah yang mempunyai iklim relatif kering. Terdapat beberapa tantangan dalam penerapannya seperti keberadaan linggan dan perubahan iklim.